ECONOMIC MECHANISMS AND POSSIBILITIES OF SUPPORTING AND STRENGTHENING FRUIT AND VEGETABLE GROWING IN UZBEKISTAN (International journal of artificial intelligence, 2025)
The article examines state support for the fruit and vegetable industry in Uzbekistan, the conditions created, economic mechanisms and opportunities. First of all, it covers issues of increasing labor productivity, linking production with science, providing personnel, and introducing new modern technologies.